THE ROLE OF NEUROINFLAMMATION IN THE PATHOGENESIS OF ALZHEIMER’S DISEASE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder and the most common cause of dementia worldwide. While amyloid-beta (Aβ) plaques and neurofibrillary tangles have long been considered the central pathological hallmarks of AD, increasing evidence highlights neuroinflammation as a critical contributor to disease onset and progression.